A interpretação da discriminação negativa no trabalho de acordo com o substancialismo - PAMPLONA, Mário Sérgio Beltrão (Universidade Federal do Pará, 2017)
The core of this thesis aims to analyze the Interpretative Theory which may extract the best conception of law on the Workplace Discrimination subject, referring to the analysis of legal discourses sustained by the theoretical aspects of the procedural legal rationality and substantive legal rationality, making the proper association with the Brazilian legal system, with emphasis on the fundamental constitutional principles and rights related to the topic. The substantial rationality shall be treated with substantial support in the fundamentals of law, living in a political morality shared and accepted in a society personified by ethical and moral principles, such as the fair treatment and respect to all and tolerance to diversity, which are rooted in the liberal-egalitarian scenario according to the concept adopted by Ronald Dworkin. In Chapter I, the taxonomy of Workplace Discrimination shall be discussed, dealing with this topic under the context of the fundamental rights, elements of the principles‟ theory and the public interest, revealing thus the nature of a difficult case. On the second chapter, the approach refers to the legal rationalization process when a court decision is to be given - turning evident the relationships between rationality and language, the relevance of the method, with emphasis to the topic‟s problematizing bias and systematic thinking. In chapter III, discussion will be made on procedural rationality according to Robert Alexy, considered the criticism addressed to both the topic and systematic thinking, on the aforementioned author‟s constructive process of legal argumentation theory. Fourth chapter focuses the substantial rationality according to the Ronald Dworkin‟s integrity theory, pointing out the principles of political morality which are the very foundation of the Law‟s integrity – which substantively may interdict the judicial discretion during legal interpreting, leading to a correct answer positively parameterized by the principles and fundamental rights.